A reinterpretation of The Hague child abduction convention to protect children from exposure to sexism, mysogyny and violence against women - Pretelli, Ilaria (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
The 1980 Hague Convention benefits from the 2011 Istanbul Convention which makes violence against women visible as a global phenomenon. A sexist culture may explain abductions by fathers, but also by mothers fleeing violence. Violence against women is a wider phenomenon as compared to domestic violence, although both are structurally linked to the historical subordination of women. Such subordination has naturally led to a proprietary view of the family even in advanced socio-cultural contexts. In the perspective of the best interests of the child, the distinction between wrongful transfers of a child’s residence by his or her primary caregiver and abductions in the strict sense deserves to be reconsidered.
Keywords: Rights of the child; Istanbul Convention; Violence against women; domestic violence; gendered-based violence; international child abduction; best interests of the child; the Hague Child Abduction Convention; Brussels IIbis (Regulation 2201/2003); Brussels IIter (Regulation 1111/2019)